Toxicity Test of Fixed Dose Method on Ethanol Extract of Ramania Leaves (Bouea macrophylla Griffith.) from South Kalimantan - Aryzki, Saftia; Gaghauna, Eirene E. M.; Kusuma, Citra Agustiani (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Acute oral toxicity is a side effect that occurs in a short time through single oral administration or repeated doses within 24 hours and can occur in any organ of the body, one of which is the liver. Ramania (Bouea macrophylla Griffith.) is a herbal plant that has antioxidant properties and inhibits free radicals. The animals used in this study were female white rats of the Wistar strain. Acute toxicity tests were carried out orally with a fixed dose method on 4 groups of animals with dose groups of 50 mg/kgBW, 300 mg/kgBW, 2000 mg/kgBW and 5000 mg/kgBW. Each group consisted of 5 test animals. Observations were made on LD50, clinical conditions, body weight and pathological conditions of the test animals. Observations were made for 24 hours then continued until the 14 days. The results of this study were that there was no death of animals in all groups of test animals during the observation, namely the test animals did not experience diarrhea, aggressiveness, changes in breathing and significant changes in motor activity. In clinical conditions, hair loss occurred in the test animals. Based on the body weight of the test animals from 4 observation groups, a sig value of > 0.05 was obtained, meaning that there was no significant change in the body weight of the test group. From the results obtained by the BB group before treatment and the BB group on the 7th day with values of 0.921 and 0.314, there was no significant change in the body weight of the test group. However, in the BB group 14 with a value of 0.031 there was a significant difference in the body weight of the test group. Based on the toxicity test guidelines from BPOM RI, it can be concluded that it has an LD50 > 5000 mg/kg BB with a classification of non-toxic to animals and the administration of high doses of Ramania leaf ethanol extract (Bouea marcrophylla Griffith) orally to Wistar strain rats causes gastric ulcers.